2022
DOI: 10.1002/ejsp.2816
|View full text |Cite
|
Sign up to set email alerts
|

The multiple meanings of the gender‐inclusive pronoun hen: Predicting attitudes and use

Abstract: The Swedish gender-inclusive pronoun hen can be used generically (referring to anyone), or specifically (referring to non-binary gender identities). Three studies tested evaluations and use of hen, and individual-level predictors. In Study 1 (N = 2145), specific hen was slightly favoured over generic hen. In Study 2 (N = 297), hen was more negatively evaluated than binary pronouns, and generic hen was more positively evaluated than specific hen. In Study 3 (N = 450), hen was less frequently used compared to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…For example, would it be possible to introduce a new personal pronoun that more explicitly captures people of all genders? Such reforms have been successful in languages with gendered pronouns, such as Swedish (Renström et al, 2022). It may also be possible to redefine the gender-neutral pronouns o and hän to become more associated with women and also nonbinary individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, would it be possible to introduce a new personal pronoun that more explicitly captures people of all genders? Such reforms have been successful in languages with gendered pronouns, such as Swedish (Renström et al, 2022). It may also be possible to redefine the gender-neutral pronouns o and hän to become more associated with women and also nonbinary individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, they explore the social perception of the label “nonbinary person” rather than the social perception of the individual who cannot be spontaneously classified into traditional gender categories. Other studies have explored, in turn, an understanding, perception, and processing of nonbinary linguistic forms (Hekanaho, 2022; Hernandez, 2020)—not infrequently in isolation from attitudes toward their users (Bradley et al, 2019; Renström et al, 2021).…”
Section: Social Perception Of Transgender and Nonbinary Peoplementioning
confidence: 99%
“…Nonbinary language is defined as a mode of expression that is inclusive toward people who do not identify as either man or woman. This is close to “gender-neutral language,” which, however, often refers also to avoiding talking about gender to empower women rather than talking about it in a nonbinary way and in the context of people who identify as nonbinary (Renström et al, 2021). The nonbinary language represents nontraditional gender categories, and its use can be seen as respecting diversity in terms of gender identities.…”
Section: Nonbinary and Gender-neutral Languagementioning
confidence: 99%
“…Singular they has previously been used primarily as a generic pronoun, but its use as a nonbinary pronoun is increasing (Bradley, 2020). This means that both ze and they can be assumed to have dual meanings, but given their history, the interpretation of these pronouns in text may be associated with different meanings (Renström, 2023). Given that singular they has historically been used generically, it is plausible that singular they still may serve this function in a similar way that generic he mainly is associated with masculinity (Bem & Bem, 1973).…”
Section: Pronouns and Gendermentioning
confidence: 99%
“…Instead, today's use of hen originates in the Swedish LGBTQI+ community, where it was introduced in the early 2010s as a nonbinary pronoun for individuals not identifying as women or men. Around the same time, feminist activists and scholars suggested that hen could also be used as a generic pronoun to replace the paired pronouns he/she ( han/hon ; Gustafsson Sendén et al., 2015; Milles, 2011; Renström et al., 2022). The introduction of hen resulted in a heated public debate, which was partly the reason why the word quickly became known to the general public.…”
Section: Introductionmentioning
confidence: 99%